Laboratory Diagnosis of Renal Disorders: Automated Urine Sediment Analyzer Compared with Manual Methods - K, Sharanya; Kumar, Prasanna N (Annals of Pathology and Laboratory Medicine, 2019)
BACKGROUND: Urinalysis is one of the earliest methods used to screen and detect patients with kidney diseases. It also helps to monitor and assess the severity of the disease process in already diagnosed patients. Microscopy plays a vital role in routine urinalysis and gives more information when analyzed together with chemical strip tests. Introduction of automation of the conventional methods of urinalysis has reduced the disadvantages of manual methods in terms of accuracy of results and turnaround time. METHOD: Aim of the present study is to evaluate the performance of an automatic urinalysis system – FUS-100 (which in cooperates an automatic urine chemistry analyzer H-800) manufactured by Dirui Industrial Co. Ltd., China in patients with renal diseases and compare the results of microscopy with manual microscopic analysis. In addition, our study aims to find out the possibility of safely reducing the number of manual microscopy analyses by cross-interpretation of the results generated by FUS-100 automated urine particle analyzer with manual methods. The urine sediments of five hundred urine samples were examined by these two methods. RESULT Automation of urine analysis decreases the turnaround time and is less labour intensive leading to better accuracy and precision. CONCLUSION Preanalytical errors related to centrifugation and sediment preparation are prevented in automation. Our study tends to suggest that automation of urine microscopy therefore is a more standardized procedure and makes urine microscopy a more objective investigation.